The effects of constipation on the quality of life of children and mothers - Dolgun, Eda; Yavuz, Meryem; Çelik, Ahmet; Ergün, M. Orkan (The Turkish Journal of Pediatrics, 2013)
This study, a quasi-experimental study, was planned to investigate the effects of functional constipation on the quality of life (QOL) of children and their mothers. The sample of the study included children with functional constipation and its complications and their families (n=26). The Pediatric Quality of Life Inventory (PedsQL) and Short Form Health Survey-36 (SF-36) were used. No statistically significant difference was found by SF-36 QOL scale scores of the first and sixth month interviews with the mothers. There was a statistically significant difference in total psychosocial scores of the children. When the PedsQL scores, which were completed during the first and sixth month interviews with the mothers, were compared, there were no statistically significant differences between total physical health scores, total psychosocial scores and total inventory scores.